Evaluation of Cervical Intraepithelial Neoplasia Occurrence Following the Recorded Onset of Persistent High-Risk Human Papillomavirus Infection: A Retrospective Study on Infection Duration - Lazare, Cordelle; Xiao, Songshu; Meng, Yifan; Wang, Chen; Li, Wending; Wang, Yi; Chen, Gang; Wei, Juncheng; Hu, Junbo; Xue, Min; Wu, Peng (Frontiers in Oncology, 2019)
Objectives: Persistent high-risk human papillomavirus infection is a major factor in the development of cervical intraepithelial neoplasia and cervical cancer. However, the exact point during this infection that cervical intraepithelial neoplasia develops has eluded researchers. Therefore, we designed a study investigating infection duration between the recorded onset of persistent high-risk human papillomavirus infection and cervical intraepithelial neoplasia development. Methods: Basic descriptive statistics, including the Chi-square test and the Kaplan-Meier method, were used to retrospectively analyze data of 277 women who underwent human papillomavirus genotyping, exhibited persistent high-risk human papillomavirus infection, were cervical cytology negative at enrollment, and developed cervical intraepithelial neoplasia at some point during follow-up. Results: Mean number of cervical cytology and human papillomavirus tests was 2.31 per patient (range: 2–8). Human papillomavirus 16, 52, 58, and 33 accounted for 21.64% (132/610), 21.64% (132/610), 15.90% (97/610), and 10.66% (65/610) of infections, respectively. 42.24% (117/277) and 57.76% (160/277) of women were diagnosed with cervical intraepithelial neoplasia 1 and cervical intraepithelial neoplasia 2+ after persistent high-risk human papillomavirus infection, with mean follow-up times of 18.15 (11.81) and 19.82 (13.31) months, respectively. Cervical intraepithelial neoplasia occurred between 4 and 70 months following the recorded onset of persistent high-risk human papillomavirus infection and 73.65% (204/277) of women developed cervical intraepithelial neoplasia within 24 months. Conclusion: Human papillomavirus 16, 52, 58, and 33 were the most prevalent high-risk human papillomavirus types in a group of women in which the majority developed cervical intraepithelial neoplasia within 24 months of persistent infection.